DISTRIBUTION DOSE IN HAND SYNOVIAL SARCOMA: THE ROLE OF BOLUS IN 3D-CRT - Tsaltsah Khoiriyah; Shinta Gunawati Sutoro; Muhammad Irsal; Guntur Winarno; Fitrus Ardoni; Rahadian Ahmad Maulana (Faculty of Vocational Studies, Universitas Airlangga, 2026)
Background: Synovial sarcoma is a rare soft tissue tumor, accounting for approximately 5 – 10% of all soft tissue sarcoma cases. It most commonly affects the hands and feet. Purpose: This study aims to examine the application of Three-Dimensional Conformal Radiation Therapy (3D-CRT) in treating monophasic synovial sarcoma of the hand with a specific focus on the use of a bolus to optimize the radiation dose distribution. Method: This research involves participatory observation of the patient undergoing 3D-CRT program carried out at Radiotherapy Department of MRCCC Siloam Hospital Semanggi. The research evaluates the impact of bolus application on enhancing the radiation dose delivery to the skin surface and achieving a more consistent dose distribution within the tumor target volume. Result: This research findings indicate that the use of a bolus in 3D-CRT effectively improves radiation dose coverage on the skin surface and ensures a more consistent dose distribution within the tumor target volume. Conclusion: The research highlights the important role of bolus application in enhancing the treatment efficacy for monophasic synovial sarcoma of the hand, clearly suggesting that it is a crucial factor in optimizing the radiation therapy outcomes.